Estimation of a wasted heat during ND : Yag laser pumping process - 446193 Nor Aziawati Azahari; Johari Adnan; Noriah Bidin, 1957-; Malaysian Science and Technology Congress (2004 : Sri Kembangan, Selangor) (Skudai : Universiti Teknologi Malaysia, 2004)
40